PENGARUH ADANYA PEMBANGUNAN BERKELANJUTAN TERHADAP KESENJANGAN EKONOMI DI INDONESIA - Aminda, Annisa; Aminda, Renea Shinta (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
The implementation of development in the past only emphasized the goals of economic progress which had an impact on environmental damage and social problems. Sustainable Development Approach is essentially a development activity that integrates economic, social, and environmental aspects. The purpose of this study is to find out whether Sustainable Development has an Effect on Economic Gaps in Indonesia. The method used in this research is the descriptive qualitative method. The results of this research explain that, although Sustainable Development in Indonesia produces fairly stable economic growth every year, but it has not been able to solve the problem of economic disparity between regions. Therefore, the government has a policy to relocate the capital city, with the aim that the concept of sustainable development in Indonesia can run well so that the problem of economic gaps can be solved.